2012
DOI: 10.17226/14666
|View full text |Cite
|
Sign up to set email alerts
|

Uses of Social Media in Public Transportation

Abstract: The nation's growth and the need to meet mobility, environmental, and energy objectives place demands on public transit systems. Current systems, some of which are old and in need of upgrading, must expand service area, increase service frequency, and improve efficiency to serve these demands. Research is nec essary to solve operating problems, to adapt appropriate new technologies from other industries, and to introduce innovations into the transit industry. The Transit Cooperative Research Program (TCRP) ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 1 publication
1
53
0
1
Order By: Relevance
“…The graph below summarizes some of the findings from the Pew Research Center's survey. (Bregman, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The graph below summarizes some of the findings from the Pew Research Center's survey. (Bregman, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is also used for community building and branding, networking, recruiting and indepth discussions. Reasons cited by agencies for using social media included provision of timely updates, communication of public information, citizen engagement, employee recognition and entertainment (Bregman, 2012). Social media has become part of the agencies' marketing plans, but has also been used as a planning and emergency management tool.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It cites Pew Center research in reporting that minority Americans are more likely than white Americans to believe that government use of electronic communications helps keep citizens informed. Nearly one-third of African Americans and Hispanics said it was "very important" for government agencies to post information and alerts on social networks compared to only 17 percent of white Americans (Bregman 2012). Indeed, a large percentage of focus group participants were technology savvy and indicated that they relied on their smart phones and computers to access information about public transit.…”
Section: Promotional Itemsmentioning
confidence: 99%